Roles and success factors of community health nurses in providing health care for people with disabilities in southern Thailand: a qualitative descriptive study - Tongyoy, Todsaporn; Piyabanditkul, Lukawee; Nuntaboot, Khanitta (Universitas Airlangga, 2025)
Introduction: People with disabilities (PWDs) are considered a vulnerable group due to their condition, which makes it difficult for them to access the services provided. Community health nurses (CHNs) are considered a key mechanism for supporting the implementation of activities that promote the quality of life of PWDs in the community. Therefore, this qualitative study aims to describe the role of CHNs in providing health care to PWDs in southern Thailand. Methods: A qualitative descriptive study was conducted from May 2024 to October 2024 in southern Thailand. Data were collected through in-depth interviews, observations, and focus group discussions (FGDs). Data collection continued until saturation was achieved. A total of 39 participants were divided into five groups composed of 1) CHNs; 2) Village headman; 3) Village Health Volunteers (VHVs); 4) PWDs; and 5) family caregivers were recruited based on inclusion criteria using a purposive sampling technique. Data were analyzed using thematic analysis. Results: Two themes were identified in this study: 1) CHNs’ role in providing health care for PWDs, and 2) Key factors affecting the success of CHNs in providing health care for PWDs. Conclusions: The findings revealed the significant roles of CHNs in providing health care for PWDs. Prioritizing disability care in community settings is essential. Systematic data collection and utilization can enhance care effectiveness. Capacity development programs for CHNs in disability care management are needed, and collaborative partnerships with relevant organizations should be strengthened. Policymakers must develop comprehensive strategies to optimize CHNs’ roles in community-based disability care.